Liquidity and stock returns-evidence from UK stock market - Le, Dang Thuy Trang (2013)
Liquidity has been acknowledged to affect stock returns due to its importance to investors, financial markets, and listed companies. Although there is abundant literature documenting the liquidity-stock returns relationship, results about this relationship are mixed. This might be due to the reasons that liquidity has various meanings and methods of measurements. The purposes of this study are to provide definition of liquidity in relation to stocks, introduce measures of liquidity and examine the relationship between liquidity and stock returns based on a sample of FTSE100 companies over the period from 2009 to 2012. The intuition of this study is that liquidity is negatively related to stock returns as rational investors would require a higher rate of return for holding illiquid stocks. Three panel estimation models including pooled OLS, fixed effect model and random effect model are applied and tests are conducted to determine which model is the most appropriate to base the analysis on. The results show that the pooled OLS with robust standard errors is the best model. Overall, it is revealed that the intraday price range and trading volume have statistically significant and negative effects on stock returns. On the other hand, the turnover rate and Amihud’s ILLIQ measure are positively correlated with stock returns. The bid-ask spread, a widely used measure of transaction costs dimension of liquidity in both theoretical and empirical literature, is insignificant as Petersen and Fialkowski (1994) and several others proposed that the bid-ask spread might not fully capture the transaction costs.